UEFA Champions League study: a prospective study of injuries in professional football during the 2001-2002 season - Walden, M.; Hägglund, M.; Ekstrand, J. (British Journal of Sports Medicine, 2005)
Background: No previous study on adult football involving several different countries has investigated the incidence and pattern of injuries at the highest club competitive level.